Efficient Gene Knock-out and Knock-in with Transgenic Cas9 in Drosophila. Issue 5 (1st May 2014) - Xue, Zhaoyu; Ren, Mengda; Wu, Menghua; Dai, Junbiao; Rong, Yikang S; Gao, Guanjun
Abstract: Bacterial Cas9 nuclease induces site-specific DNA breaks using small gRNA as guides. Cas9 has been successfully introduced into Drosophila for genome editing. Here, we improve the versatility of this method by developing a transgenic system that expresses Cas9 in the Drosophila germline. Using this system, we induced inheritable knock-out mutations by injecting only the gRNA into embryos, achieved highly efficient mutagenesis by expressing gRNA from the promoter of a novel non-coding RNA gene, and recovered homologous recombination-based knock-in of a fluorescent marker at a rate of 4.5% by co-injecting gRNA with a circular DNA donor.